The Use of Digital Media Quizziz Improves Mathematics Learning Outcomes in Elementary Schools - Dhea Paramitha; Berta Apriza (LPPM Undiksha, 2026)
Mathematics learning in elementary schools is important for developing logical thinking and problem-solving skills from an early age. However, many students struggle to grasp abstract concepts, leading to lower learning outcomes. The purpose of this study is to analyze the effectiveness of using the digital media Quizizz on mathematics learning outcomes in elementary schools by reviewing various relevant studies. This study examines the effectiveness of Quizizz using a Systematic Literature Review (SLR) by analyzing 10 articles from Google Scholar published between 2020 and 2024. The study's results indicate that regular Quizizz use has a positive impact on mathematics learning outcomes, particularly conceptual understanding, numeracy skills, and critical thinking. This effectiveness is seen in various learning models such as Game-Based Learning, Team Games Tournament, STAD, RME, and Problem-Based Learning. Overall, Quizizz has proven to be an effective digital medium for supporting mathematics learning in elementary schools, especially when supported by strong infrastructure and planning. The implications of this research indicate that Quizizz can be an innovative alternative to improve the quality of mathematics learning in elementary schools. The use of Quizizz also encourages more interactive, fun, and student-centered learning, thereby increasing student motivation and involvement in the learning process.